Identifying active factors by a fractioned factorial experimental design and simulation in road traffic accidents - Santos, Maria Izabel dos (2017)
Researchers around the world are constantly seeking for a quick, inexpensive and easy to use way to understand road traffic deaths. This study proposes the use of multibody (MBS) simulation, using a virtual driver, associated to fractional factorial experiments to identify active factors in road traffic accidents. The objectives of this work were to: (i) use DOE to show a more structured direction on the studies of road safety and (ii) investigate possible vehicle state variables to monitor vehicle dynamic stability. The first experiment was a quarter fraction It was designed based on an accident database of a Brazilian Federal Highway. Seven factors were considered (curve radius, path profile, path condition, virtual driver skill, speed, period of the day and car load) and 3 replicates were performed per treatment. Speed and friction coefficient were defined randomly for each treatment, within the defined range for each level. 42 accidents were observed in 96 events. Speed had shown the highest influence on the occurrence, followed by curve radius, period of the day and some second order interactions. The second experiment was based on the results of first one. A half fraction factorial design with five factors (curve radius, car load, virtual driver skill, period of the day and speed), with 14 replicates per treatment, was performed. Speed was defined randomly as per previous experiment. 96 accidents were observed in 224 events. Speed had the highest influence on the occurrence of accidents, followed by the period of the day, curve radius, virtual driver skill and second order interactions. Speed is also pointed by World Health Organization as one of the key factors for the occurrence of accidents. The study indicates that a well-designed experiment with a representative vehicle model can show a direction for further researches. At last, roll angle, yaw rate and displacement of the car on the road are variables suggested to be monitored in experiments using simulation to identify vehicle\'s instability.